2007
DOI: 10.1007/s10038-007-0215-5
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of DNA repair gene XPC polymorphisms and cancer risk

Abstract: Polymorphisms (A33512C, C21151T and PAT -/+) of the xeroderma pigmentosum group C (XPC) were shown to contribute to genetic susceptibility to cancer. However, association studies on these polymorphisms in cancer have shown conflicting results. Thus, we performed a meta-analysis. Overall, there was no significant association between 33512C (9,091 patients and 11,553 controls) and cancer risk. No significant association was found in stratification analysis by tumor sites and ethnicities except an elevated lung c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 38 publications
1
31
2
2
Order By: Relevance
“…Only a minority of studies have reported case -control data on the same variants, allowing pooling of data (Table 1). Although P-values from meta-analyses of such studies provide limited support for the role of variants in MTHFR (Huang et al, 2007;Hubner and Houlston, 2007), CCND1 (Tan et al, 2008), GSTT1 (de Jong et al, 2002), XPC (Zhang et al, 2008), NQO1 (Chao et al, 2006) and NAT2 (Chen et al, 2005), such analyses should be interpreted with caution even if publication bias is ignored. Use of false-positive report probability value (FPRP) (Wacholder et al, 2004), which integrates the earlier probability for association and statistical power, provides one method for assessing the robustness of summary estimates derived from pooled analyses.…”
Section: Difficulties In Conducting Methodologically Rigorous Associamentioning
confidence: 99%
“…Only a minority of studies have reported case -control data on the same variants, allowing pooling of data (Table 1). Although P-values from meta-analyses of such studies provide limited support for the role of variants in MTHFR (Huang et al, 2007;Hubner and Houlston, 2007), CCND1 (Tan et al, 2008), GSTT1 (de Jong et al, 2002), XPC (Zhang et al, 2008), NQO1 (Chao et al, 2006) and NAT2 (Chen et al, 2005), such analyses should be interpreted with caution even if publication bias is ignored. Use of false-positive report probability value (FPRP) (Wacholder et al, 2004), which integrates the earlier probability for association and statistical power, provides one method for assessing the robustness of summary estimates derived from pooled analyses.…”
Section: Difficulties In Conducting Methodologically Rigorous Associamentioning
confidence: 99%
“…Thus, it may play a role in the pathogenesis www.intechopen.com of HCC-related AFB1. Some recent studies have showed that defects in XPC have been related to many types of malignant tumors (73)(74)(75)(76)(77)(78)(79)(80)(81)(82). Transgenic mice studies also revealed predisposition to many types of tumors in XPC gene knockout mice (83).…”
Section: Genetic Polymorphisms In Genes Involved In Ner Pathway and Rmentioning
confidence: 99%
“…Son za man lar da ya yın lan lan iki me ta ana liz de, nük le o tit ek siz yon ona rı mın da rol alan Xe ro der ma pig men to sum C (XPC) ge ni Ala499Val var yan tı nın me sa ne kan se ri ris ki ni ar tır dı ğı bil di ril miş tir. 138,139 Wu ve ark., 140 XPD Asp312 al le li nin, me sa ne kanse ri ris ki ni %28 ar tır dı ğı nı bil dir miş tir. Ga o ve ark.…”
Section: Kar Si̇ No Jen Me Ta Bo Li̇ Ze Edi̇ Ci̇ Gen Ler Ve Po Li̇ Mor Fi̇zmunclassified